2012
DOI: 10.15288/jsad.2012.73.1005
|View full text |Cite
|
Sign up to set email alerts
|

Not All Those Who Wander Are Lost: Examining the Impact of Sojourner Adjustment and Drinking Motives on Alcohol Consequences Experienced by Americans Studying in Foreign Countries

Abstract: ABSTRACT. Objective: American students studying in foreign countries represent a unique group at risk for increased and problematic drinking. Examination of risk and protective factors for negative alcohol-related consequences can lead to the development of effi cacious preventive interventions for reducing high-risk drinking while abroad. The present study examined the relationship between sojourner adjustment (i.e., the sociocultural and psychological adjustment of short-term residents in foreign environment… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
31
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 18 publications
(33 citation statements)
references
References 50 publications
2
31
0
Order By: Relevance
“…Poor language proficiency predicted social difficulty and reduced sociocultural adjustment among foreign students (Ward & Kennedy, 1993b) and barriers to communication with local people are suggested to predict adjustment difficulty (Church, 1982;Dillion, 1993;Heikinheimo & Shute, 1986). For American study abroad students, the language development and use factor of the SAM had the strongest unique effect on prediction of fewer alcohol-related consequences while abroad (Pedersen et al, 2011d). Moreover, study abroad students in this same sample who reported drinking for more social facilitation reasons who also reported difficulties with language development and use experienced greater numbers of alcoholrelated consequences abroad.…”
Section: Adjustment/transition To Life In a Foreign Environment --Sojmentioning
confidence: 80%
See 4 more Smart Citations
“…Poor language proficiency predicted social difficulty and reduced sociocultural adjustment among foreign students (Ward & Kennedy, 1993b) and barriers to communication with local people are suggested to predict adjustment difficulty (Church, 1982;Dillion, 1993;Heikinheimo & Shute, 1986). For American study abroad students, the language development and use factor of the SAM had the strongest unique effect on prediction of fewer alcohol-related consequences while abroad (Pedersen et al, 2011d). Moreover, study abroad students in this same sample who reported drinking for more social facilitation reasons who also reported difficulties with language development and use experienced greater numbers of alcoholrelated consequences abroad.…”
Section: Adjustment/transition To Life In a Foreign Environment --Sojmentioning
confidence: 80%
“…Goals of enhanced cultural competency prior to departure associate with increased global understanding and cross-cultural skill development after study abroad trips (Kitsantas, 2004). Surprisingly, researchers found this factor to be predictive of increased rates of alcohol-related consequences abroad after controlling for the other three positive Sojourner Adjustment factors (Pedersen et al, 2011d). Nevertheless, cultural understanding has still been retained as a positive factor of Sojourner Adjustment.…”
Section: Adjustment/transition To Life In a Foreign Environment --Sojmentioning
confidence: 96%
See 3 more Smart Citations